Diplomasi Indonesia dalam Menyelesaikan Krisis Pengungsi Rohingya Tahun 2017 - Albayumi, Fuat; Hadi, Nourma Meysita; Susilo, Djoko (Nation State: Journal of International Studies, 2018)
The armed conflict in Rakhine in 2017 caused a humanitarian crisis for the Rohingyas. This crisis resulted in the emergence of criticism towards Myanmar government for its refusal to offer humanitarian assistance to the victims of conflict. In spite of that, the Myanmar government has closed access for foreigners, including humanitarian aid. However, Indonesia have accepted to discuss the settlement of the case. This research will examine how Indonesia's diplomacy to resolve the crisis due to the conflict in Rakhine in 2017. This research uses research literature method to collect secondary data coming from reliable source. This research is using qualitative descriptive technique and analyzed to described or interpreted to obtain a complete picture of the answer to the problem under study. The results show that in resolving the crisis for Rohingya ethnic in 2017, Indonesia conducts humanitarian diplomacy, which includes communicating with the Myanmar and Bangladesh governments and foreign parties, acting as a liaison between the Myanmar government and the international community, and negotiating with Myanmar and Bangladesh governments regarding the settlement of the Rohingya refugee crisis.